GENETIC VARIABILITY IN JUVENILE CHARACTERS OF PROGENIES OF Apuleia leiocarpa - Lovatel, Queli Cristina; Navroski, Marcio Carlos; Gerber, Tamara Rosa; de Oliveira, Luciana Magda; Pereira, Mariane de Oliveira; Silveira, Maiara Fortuna (Floresta, 2021)
The objective of this search was to quantify the genetic variability in progenies from grápia mother trees in natural populations, for initial growth characters of the seedlings. Seeds were collected from 13 mother trees, from four origins, located in the municipalities of Pareci Novo, São José do Sul and Aratiba in RS, and Seara in SC, as well as data from plants and place of origin. Biometrics were performed on 100 seeds lot from each mother tree, and an experiment was installed to evaluate progenies in a completely randomized design. It was evaluated the seedling emergence speed and the emergence percentage, the stem diameter and seedlings height, as well as the final survival percentage. A significative difference was found for all variables observed for seeds and seedlings of grápia mother trees. Seed length and width demonstrated high values for individual heritability in the narrow sense (above 0.6), being possible to use the seed size for an analysis of genetic variability between plants of the species, but not as an indicative variable of physiological quality and vigor. The correlation analysis indicated that the seedling emergence percentage is related to the characteristics of the mother plant plant (height and diameter). Thus, the use of seedlings for forest restoration areas is appropriate, as they have indications of genetic diversity.